The guardians - Belfry Holdings, Inc. (Tupelo, Missouri) (New York : Doubleday, 2019)
"The newest legal thriller from #1 New York Times bestselling author John Grisham. This masterfully plotted, perfectly paced novel confirms that Grisham remains America's favorite storyteller. In the small north Florida town of Seabrook, a young lawyer named Keith Russo was shot dead at his desk as he worked late one night. The killer left no clues behind. There were no witnesses, no real suspects, no one with a motive. The police soon settled on Quincy Miller, a young black man who was once a client of Russo's. Quincy was framed, convicted, and sent to prison for life. For twenty-two years he languished in prison with no lawyer, no advocate on the outside. Then he wrote a letter to Guardian Ministries, a small innocence group founded by a lawyer/minister named Cullen Post. Guardian handles only a few innocence cases at a time, and Post is its only investigator. He travels the South fighting wrongful convictions and taking cases no one else will touch. With Quincy Miller, though, he gets far more than he bargained for. Powerful, ruthless people murdered Keith Russo, and they do not want Quincy exonerated. They killed one lawyer twenty-two years ago, and they will kill another one without a second thought"--